Leading Successfully in Asia - Low, Kim Cheng Patrick (Springer International Publishing, 2018)
This book examines the essence of leadership, its characteristics and its ways in Asia through a cultural and philosophical lens. Using Asian proverbs and other quotes, it discusses leadership issues and methods in key Asian countries including China, India, Japan, Kazakhstan, Malaysia and Singapore. It also explores the leadership styles of various great Asian political and corporate leaders. Further, it investigates several unique Asian philosophies, such as Buddhism, Guan Yin, Confucianism, Ta Mo, Chinese Animal zodiac signs, Hindu Gods, the Samurai, the Bushido Spirit and Zen in the context of leadership mastery and excellence. Offering numerous examples of a potpourri of the skills and insights needed to be a good, if not a great, leader, this practical, action-oriented book encourages readers to think, reflect and act.